Odpowiedzi

Najlepsza Odpowiedź!
2010-01-22T17:35:59+01:00
5x +3y = 15 / *(-2)
10x -6y = 0

-10x -6y= -30
10x - 6y= 0
------------
-12y = -30
y=2,5

5x + (3*2,5) = 15
5x = 15 - 7,5
5x = 7.5
x=1.5

x=1.5
y=2.5

2.
7x-10y=3 /*2
2x-3y=6 / *-7

14x - 20y = 6
-14x + 21y = -42
y= - 36

2x - (3 * - 36) = 6
2x = 6- (-108)
2x = 114
x= 57

x= 57
y= - 36
2010-01-22T18:02:25+01:00
A)
5x+3y=15 /*2
10x-6y=0

10x+6y=30
10x-6y=0

10x+6y+10x-6y=30
5x+3y=15

20x=30 /:20
5x+3y=15

x=3/2
5*3/2+3y=15
→7,5+3y=15
→3y=15-7,5
→3y=7,5 /:3
→y=2,5

x=1,5
y=2,5

b)
7x-10y=3
2x-3y=6

7x-10y=3
2x=(6+3y) /:2

x=(6+3y)/2
7*(6+3y)/2 -10y=3 /*2
→7*(6+3y)-20y=6
→42+21y-20y=6
→y=6-42
→y=-36

x=[6+3*(-36)]/2
→x=(6-108)/2
→x=-51

x=-51
y=-36

te odpowiedzi są prawidłowe ;)
1 5 1